Developing leaders for positive organizing : a 21st century repertoire for leading in extraordinary times - Vogel, Bernd, active 2017; Koonce, Rob; Robinson, Paula (Emerald Publishing Limited, 2017)
As revealed in the most recent global survey of human capital trends conducted by Deloitte University, leadership is rated as the top priority across all organizational levels, geographies, and functional areas in every industry. The evolving shift in leadership from individual leaders at the top to collective leadership throughout organizations requires creating and sustaining the necessary conditions through which leaders and those being led can flourish and positive organizing can thrive. Developing Leaders for Positive Organizing examines this challenge by taking the reader on an investigative journey into everyday leadership as framed in the increasingly interconnected context of human relationships within and across organizations around the globe. This book offers broad appeal for the novice working practitioner; corporate, not-for-profit, or non-profit executive; experienced scholar or academic student.- Resumé vydavatel